Evaluasi Program Pengendalian Tuberkulosis dengan Strategi DOTS di Eks Karesidenan Surakarta - Firdaufan; Santoso; Hartanto, Rifai; Hendratno; Sumardiyono; Sutisna, Endang; Syahril, Mohammad (Jurnal Kedokteran Indonesia, 2009)
Background: Direct Observed Treatment Short Course (DOTS) strategy has been regarded as successfulto control Tuberculosis. However decreasing rates of TB prevalence and mortality were not fastenough to attain half of the prevalence and mortality in 2015 as targeted by Millenium DevelopmentGoals (MDGs). There is a need for continuity and expansion of DOTS strategy implementation. Thisstudi aimed to evaluate the attainment of TB control program with DOTS strategy and determinefactors affecting it.Methods: This was a quantitative and qualitative evaluation study using a post-hoc cross-sectionaldesign. The study was conducted in Sukoharjo and Boyolali districts, and Surakarta municipality, CentralJava, carried out from October 2009 to February 2010. The target population included TB implementingworkers, policymakers, TB health program planners, TB patients and their family, and other stakeholders.Results: There is disparity in the target attainment of TB control program at district/ municipalities aswell as subdistrict levels. Some districts and subditricts have not reached the expected quantitativeand qualitatives levels of outcome. Case finding and detection rate were subtstandard 70%, atmunicipality/ district level. This problem was due to level of compliance among doctors, spesialists,and private hospitals was still low to implement standard procedures of diagnosis, treatment, reportingand recording of TB patients. The drop-out rate and ineffective drug administration supervision affectedthe cure rate. Financial support for the TB control program from the local government and locallegislatives was lacking.Conclusion: TB control program with DOTS has been implemented but with varying level ofachievement. System strengthening and participation of all health providers are encuraged byestablishing external network.Keywords: evaluation, tuberculosis control, DOTS strategy